PERAN DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK DAN PEMBERDAYAAN MASYARAKAT (DP3APM) DALAM MENCEGAH DAN MENANGANI KASUS KEKERASAN SEKSUAL TERHADAP PEREMPUAN DI KOTA PEKANBARU TAHUN 2021-2023 - Sitohang, Priskila Br Sitohang; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Sexual violence is any act in the form of coercion or threats to have sexual intercourse, torture or sadistic acts, and leaving women after committing sexual violence. Sexual violence is related to Sustainable Development Goals (SDGs) number 5, namely Gender Equality. The causes of sexual violence include lack of education about women's rights, public discomfort, economic conditions, discrimination against women. The research objective is to describe the role of the Office of Women's Empowerment, Child Protection and Community Empowerment (DP3APM) in preventing and handling cases of sexual violence against women in Pekanbaru City in 2021-2023. The theory used is the role theory of Ryass Rasyid with 3 indicators 1) regulator, 2) dynamizer, and 3) facilitator. The method in this research uses a qualitative approach and descriptive qualitative research type. The results of this study are based on Riyas Rasyid's theory seen in the regulator indicator, the agency has not yet established a Decree (SK) in the formation of a task force for the prevention and handling of sexual violence against women. From the dynamic indicator, it can be seen that the agency has carried out socialization, but it is more focused on the crime of trafficking in persons (TPPO). In the facilitator indicator, the agency's role in providing services has been carried out, but it still lacks human resources in carrying out its duties. The conclusion of this research is that the role of DP3APM Pekanbaru City is still not optimal in preventing and handling sexual violence against women, as can be seen from the regulator, dynamizer and facilitator indicators. Keywords: Role, Preventing, Handling, Sexual Violence Against Women